Pengaruh Kualitas Pelayanan Pajak, Tingkat Pendapatan, Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Masyarakat dalam Membayar Pajak Kendaraan Bermontor : Studi Kasus Wajib Pajak Kota Kediri Tahun 2024 - Lilis Saputri; Hestin Sri Widiawati; Sigit Puji Winarko (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Motor Vehicle Tax is one of the main sources of regional revenue, essential for supporting development and public services. However, taxpayer compliance has tended to decline despite the continuous increase in the number of vehicles. This study aims to analyze the effect of service quality, income level, and tax sanctions on motor vehicle taxpayer compliance in Kediri City. A quantitative approach with a causal research design was used. The sample consisted of 100 respondents, selected using simple random sampling with Slovin’s formula at a 10% margin of error. Data analysis was conducted using multiple linear regression with SPSS version 23. The results show that service quality does not significantly affect taxpayer compliance, while income level and tax sanctions have significant effects. Simultaneously, all three variables significantly influence compliance. These findings highlight the importance of income and strict sanctions in improving tax compliance.